Exact exchange: A pathway for a density functional theory of the integer quantum Hall effect. (14th November 2017) - Miravet, D.; Ferreira, G. J.; Proetto, C. R.
Abstract: It is shown here that the exact-exchange (EE) formalism provides a natural and rigorous approach for a density functional theory (DFT) of the integer quantum Hall effect (IQHE). Application of a novel EE method to a quasi–two-dimensional electron gas (q2DEG) subjected to a perpendicular magnetic field leads to the following main findings. i) the microscopic exchange energy functional of the IQHE has been obtained, whose main feature being that it minimizes with a discontinuous derivative at every integer filling factor ν ; ii) an analytical solution is found for the magnetic-field dependent EE potential, in the one-subband regime; iii) as a consequence of i), the EE potential display sharp discontinuities at every integer ν ; and iv) the widely used local spin density approximation (LSDA) is strongly violated for filling factors close to integer values.